2017
DOI: 10.1007/s10072-017-2833-9
|View full text |Cite
|
Sign up to set email alerts
|

Early experience with compassionate use of 2 hydroxypropyl-beta-cyclodextrin for Niemann–Pick type C disease: review of initial published cases

Abstract: Niemann-Pick type C (NP-C) is a rare neurodegenerative disorder. Management is mainly supportive and symptomatic. The investigational use of 2-hydroxypropyl-β-cyclodextrin (HP-β-CD) showed a promising role in treating NP-C, although efficacy and safety have not been established. We conducted searches of MEDLINE, Cochrane, EMBASE, and other databases of reported cases of HP-β-CD compassionate use in NP-C disease. Sixteen reported cases were eligible, including evaluable information of 17 patients. The median on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 35 publications
1
39
0
Order By: Relevance
“…Another orphan drug of HP-β-CD was designated by FDA in February 2013, Kleptose™ (brand VTS-270). Both drugs were being evaluated in clinical trials, moreover compassionate use outside clinical trials has been reported worldwide [32].…”
Section: Experience In Humans: First Experiences Of Compassionate Usementioning
confidence: 99%
See 3 more Smart Citations
“…Another orphan drug of HP-β-CD was designated by FDA in February 2013, Kleptose™ (brand VTS-270). Both drugs were being evaluated in clinical trials, moreover compassionate use outside clinical trials has been reported worldwide [32].…”
Section: Experience In Humans: First Experiences Of Compassionate Usementioning
confidence: 99%
“…After 18 months of therapy, any objective improvement was reported, and the disease continued to progress as evidenced by positron emission tomography (PET) imaging and neurological assessments [26]. Both patients were described a transient appearance of slight scattered nodules in lungs during bronchoscopy, which were identified as xanthomas, a deposition of yellowish cholesterol-rich material typical of NPD-C, resolved without treatment changes in IV therapy [32].…”
Section: Experience In Humans: Efficacy Of the Intravenous Administramentioning
confidence: 99%
See 2 more Smart Citations
“…Many reports are dedicated to rare neurologic diseases, genetic disorders describing new developments on the molecular diagnosis [121][122], the clinical heterogeneity of the clinical spectrum [123][124][125][126][127][128][129][130][131][132][133][134], and the therapeutic opportunities [135][136][137].…”
mentioning
confidence: 99%